2004
DOI: 10.1038/sj.embor.7400297
|View full text |Cite
|
Sign up to set email alerts
|

NMR structure of the bovine prion protein isolated from healthy calf brains

Abstract: NMR structures of recombinant prion proteins from various species expressed in Escherichia coli have been solved during the past years, but the fundamental question of the relevancy of these data relative to the naturally occurring forms of the prion protein has not been directly addressed. Here, we present a comparison of the cellular form of the bovine prion protein isolated and purified from healthy calf brains without use of detergents, so that it contains the two carbohydrate moieties and the part of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
118
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 30 publications
7
118
0
2
Order By: Relevance
“…90-230) with or without typical complex glycoforms indicated that glycosylation did not perturb the structure, and may even stabilize it somewhat. Although these simulations were too short to capture potential large conformational changes, NMR studies on bovine PrP purified from brain extracts indicated that the structure of glycosylated PrP (including the sugar portion of the GPI-anchor) is very similar to recPrP [161]. Recently, longer extensive MD simulations of diglycosylated PrP were reported [53]: DeMarco and Daggett performed 15 ns simulations of human PrP (res.…”
Section: In Vivo Modificationsmentioning
confidence: 99%
“…90-230) with or without typical complex glycoforms indicated that glycosylation did not perturb the structure, and may even stabilize it somewhat. Although these simulations were too short to capture potential large conformational changes, NMR studies on bovine PrP purified from brain extracts indicated that the structure of glycosylated PrP (including the sugar portion of the GPI-anchor) is very similar to recPrP [161]. Recently, longer extensive MD simulations of diglycosylated PrP were reported [53]: DeMarco and Daggett performed 15 ns simulations of human PrP (res.…”
Section: In Vivo Modificationsmentioning
confidence: 99%
“…The PrP C structure has been solved by nuclear magnetic resonance (NMR) analysis from recombinant prion protein from a library of vertebrate species [13,21,31,[45][46][47]63]. The global architecture of the various mammalian PrP structures are nearly identical.…”
Section: Prp C Structurementioning
confidence: 99%
“…So far, atomic resolution structure determination was focused on recombinant mammalian prion proteins (10)(11)(12)(13)(14)(15)(16)(17)(18), which have recently been shown to represent the protein architecture of PrP C (19). As a group, the mammalian PrPs have Ϸ90% sequence identity (4).…”
mentioning
confidence: 99%